Nilai Kehidupan Masyarakat Tionghoa (Suatu Analis Wacana Ritual Tahun Baru Imlek) - Zakki Ismail (TASAMUH: Jurnal Studi Islam, 2015)
Target of this research is to know life concepts experienced by society of Ti onghoa through prayer of Imlek. Refering to that, the question replied in this research is how discourse forms ritual of Imlek and asses also conception found in the prayer.